Uji Validitas Angket SLCQ-I pada Mahasiswa Fakultas Kedokteran Universitas Malahayati Lampung - Ahmad Zidane Sagareno; Sutarto Sutarto (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2020)
The learning process requires concentration in order to achieve the expected learning outcomes. Data from the measurement results of learning concentration will certainly be useful in evaluating learning. The availability of limited questionnaire makes research on the concentration of learning difficult to do on bachelor student. Therefore a valid questionnaire is needed to collect data. The aim of the study is to conduct a validity test of the learning concentration questionnaire on bachelor students. The method used invalidity test is observational analytic with a cross-sectional approach. The statistical test used is the Pearson Product Moment correlation and the reliability test with internal consistency. The results obtained for all items in the questionnaire validity test above 0.3 and the reliability test questionnaire value Cronbach alpha 0.924. The conclusion is SLCQ-I (Student Learning Concentration Questionnaire Indonesia Version) fulfills the validity and reliability requirements so it is declared valid and reliable.